The Ethical Dimension in the New Public Management: Revisiting the Theory of Accountability, the Case of Public Finances in Morocco - Mohamed, Akhlaffou; Youssef, El Wazani; Malika, Souaf; Hafsa, Lechheb (European Scientific Journal, ESJ, 2016)
In this paper, we focus on the positioning of the ethical theory of accountability and the relevance of the new public management in the integration of the ethical dimension in the management of public organizations and non-profit organizations. The objective is to show how the NPM and the theory of accountability incorporate the ethical dimension, and to what extent these two theories consider ethics in the construction process of public action, the sense and nonsense in public management and its relationship with the position of ethics in the management of public organizations. This will be done through a case study on the ethical dimension in the management of public finances in Morocco, proposing recommendations to make accountability in public finances more transparent and ethical.